Antibody-mediated protection against Brucella abortus in BALB/c mice at successive periods after infection: variation between virulent strain 2308 and attenuated vaccine strain 19. - Elzer, P H (1994)
In BALB/c mice antibodies specific for the O polysaccharide (OPS) as well as T lymphocytes mediate protective immunity to Brucella abortus. We performed quantitative analyses of isotypes of OPS antibodies generated during primary infections, and tested the protective qualities of antisera at successive stages of infection against B. abortus strain 2308, representative of the wild type, and attenuated vaccine strain 19. IgM antibodies predominated during the first 3-4 weeks of infection. IgG3 antibodies increased slowly for the first 3 weeks but then rose rapidly and persisted at high levels (> 300 micrograms/ml). IgG1, IgG2a and IgG2b antibodies had increased slightly by week 4 and then remained at low to moderate levels (< 70 micrograms/ml). Week 2 serum pools (IgM high, IgG3 low or undetectable) transferred substantial protection against 2308 (> or = 1 log unit) which increased relatively little (to 1.2-1.5 log units) with later sera that were high in IgG antibodies. In contrast, week 2 sera conferred low levels of protection against 19 (< 0.6 log units), but protection was dramatically increased (to > or = 2.3 log units) with sera obtained 1 week later that had slightly increased IgG antibodies. Monoclonal IgM antibodies also provided better protection against 2308 than 19, while monoclonal IgG3 antibodies protected much better against 19. Strain 19 opsonized with antibodies taken at any stage of infection was killed within normal macrophages, whereas comparably opsonized 2308 underwent intracellular replication. Phagocytosis of 2308 was better than of 19 when brucellae were opsonized with either polyclonal IgM or IgG3 antibodies, and the difference between strains was more extreme following IgM opsonization. The data suggest an explanation for differences in the growth curves of 2308 and 19 in spleens of BALB/c mice. Higher numbers achieved by 19 at week 2 could result from extracellular replication owing to ineffectual opsonization by IgM antibodies, while the precipitous decline of 19 beginning at week 3 could be caused by the increase in more effective IgG3 opsonins that facilitate its rapid intracellular destruction.